Transjugular Intrahepatic Portosystemic Shunt for the Treatment of Portal Hypertension in Noncirrhotic Patients with Portal Cavernoma - Xuefeng Luo; Ling Nie; Biao Zhou; Denghua Yao; Huaiyuan Ma; Mingshan Jiang; Hailong Zhang; Xiao Li (Gastroenterology Research and Practice)
Background. The purpose of this study was to evaluate the safety and efficacy of transjugular intrahepatic portosystemic shunt (TIPS) placement in the management of portal hypertension in noncirrhotic patients with portal cavernoma. Methods. We conducted a single institution retrospective analysis of 15 noncirrhotic patients with portal cavernoma treated with TIPS placement. 15 patients (4 women and 11 men) were evaluated via the technical success of TIPS placement, procedural complications, and follow-up shunt patency. Results. TIPS placement was technically successful in 11 out of 15 patients (73.3%). Procedure-related complications were limited to a single instance of hepatic encephalopathy in one patient. In patients with successful shunt placement, the portal pressure gradient decreased from 25.8±5.7 to 9.5±4.2 mmHg (P<0.001). TIPS dysfunction occurred in two patients during a median follow-up time of 45.2 months. Revision was not performed in one patient due to inadequate inflow. The other patient died of massive gastrointestinal bleeding in a local hospital. The remaining nine patients maintained functioning shunts through their last evaluation. Conclusions. TIPS is a safe and effective therapeutic treatment for noncirrhotic patients with symptomatic portal hypertension secondary to portal cavernoma.